Steven Johnson syndrome in patients with complications of elevated Alt and Ast levels: A Case Report - Tavia Yuliastuti Prastika; Fiedyia Wati Kusuma; Stevia Artha Natalia Purba (Jurnal EduHealth, 2023)
Stevens-Johnson syndrome (SSJ) is an extremely rare, acute, and potentially life-threatening event; is an immune complex-mediated hypersensitivity reaction that is often associated with drug use. The aim of this study is to describe the Steven Johnson Syndrome experienced by patients with complications of increased ALT and AST levels. The patient is a 58-year-old male with complaints of red spots all over the body and fever before being admitted to the hospital. The skin rash increases in redness all over the body, there are loose and then burst bullae on the neck, chest, and back, it feels sore and burning, there are dry scars on the lips, nose, and ears, accompanied by complaints of red eyes, painful swallowing, and occasional coughing. The patient took dexamethasone, paracetamol, and allopurinol before symptoms appeared. The most common complications in SJS cases are respiratory problems including bronchopneumonia and moderate increases in transaminase enzyme levels that do not cause jaundice. Stopping previous drug consumption and prompt and appropriate treatment can reduce mortality rates.